Revising the penetration behavior of concrete-like and metal-like materials against the rigid projectile impact. (March 2020) - Mu, ZhongCheng; Zhang, Wei; Wang, Wei; Jiang, NingJing; Wu, Xiaofeng
Highlights: Issue that the reason behind the quasi-constant behavior in the tunneling penetration stage of the rigid penetration mode for both metal-like and concrete-like material targets. Two-phase penetration theory under the rigid penetration mode was discussed and validated for both metal-like and concrete-like target materials. The role of the friction effect during the rigid penetration process was investigated. Abstract: Many studies indicate that projectile deceleration exhibits a quasi-constant behavior in the tunneling penetration stage of the rigid penetration mode for both metal-like and concrete-like materials. As to the issue, in the present paper the penetration process under the rigid penetration mode was revised, where a two-phase penetration theory is proposed including the 'Squeeze and Push' penetration phase and the dynamic spherical cavity expansion penetration phase. When the striking velocity is below the critical striking velocity, the 'Squeeze and Push' effect is generated since the cavitation size is less than the projectile diameter, where the quasi-static term overshadows the dynamic term. The interaction from the surface friction between projectile and target and the penetration force due to the main quasi-static term contributes to the occurrence of the quasi-constant phenomenon. Conversely, when the striking velocity is above the critical velocity, the penetration enters into the dynamic spherical cavity expansion penetration phase, the accompanying feature is that the tunnel becomes large beyond the projectile diameter, meanwhile the friction effect between the projectile and target disappears, the deceleration shows a well-defined peak with the rise of the striking velocity. Following the features, semi-empirical formulas are obtained. Finally, the semi-empirical formulae are discussed and validated by comparing with the typical penetration experiments including concrete-like and metal-like materials.